The Impact of Introducing Low Traffic Neighbourhoods on Road Traffic Injuries - Anthony A Laverty; Rachel Aldred; Anna Goodman (Findings, 2021)
We examine the impact on road traffic injuries of introducing low traffic neighbourhoods in Waltham Forest, London. Using Stats19 police data 2012-2019, we find a three-fold decline in number of injuries inside low traffic neighbourhoods after implementation, relative to the rest of Waltham Forest and the rest of Outer London. We further estimate that walking, cycling, and driving all became approximately 3-4 times safer per trip. There was no evidence that injury numbers changed on boundary roads. Our findings suggest that low traffic neighbourhoods reduce injury risks across all modes inside the neighbourhood, without negative impacts at the boundary.